Foundations of Efficient Supervision Over the Global Finance Market - Szapiel, Jolanta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
The extent of the latest financial crises provokes reflection on many aspects of the functioning of modern financial markets. In the scientific discourse, the notion of institutional conditions in a broad sense as a source of the current financial crisis is prominently featured.This article perfectly fits in the deliberation on this subject. The author attempts to explain theproblem of the supervision structure over the global financial market utilizing the findings of the new institutional economics.
Keywords: functions of states on the market institutions; global financial market; oversight of financialmarket; cooperation; coordination; institutions